Open Source Knowledge Development Seminar for the Education Sector. - Anuwar Ali, (Open University Malaysia (OUM), 2004)
Speech of the President/Vice-Chancellor OUM, Prof Tan Sri Anuwar Ali on seminar of Open Source Knowledge Development Seminar for the Education Sector at Theaterette, OUM on 29th March 2004.